2021
DOI: 10.3389/fonc.2021.698427
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Treatment Response of Neoadjuvant Chemoradiotherapy in Locally Advanced Rectal Cancer Using Amide Proton Transfer MRI Combined With Diffusion-Weighted Imaging

Abstract: ObjectiveTo evaluate amide proton weighted (APTw) MRI combined with diffusion-weighted imaging (DWI) in predicting neoadjuvant chemoradiotherapy (NCRT) response in patients with locally advanced rectal cancer (LARC).Methods53 patients with LARC were enrolled in this retrospective study. MR examination including APTw MRI and DWI was performed before and after NCRT. APTw SI, ADC value, tumor size, CEA level before and after NCRT were assessed. The difference of the above parameters between before and after NCRT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…These studies (16,19,27) have found additional valuable perspectives using multi-modal MRI analysis. Furthermore, in some studies (29), tumor regression degree (mrTRG) on MRI was determined based on changes in tumor size and signal intensity on T1, T2, and WI to predict the outcome of NCRT. Unfortunately, as demonstrated, there is no pathological gold standard.…”
Section: Introductionmentioning
confidence: 99%
“…These studies (16,19,27) have found additional valuable perspectives using multi-modal MRI analysis. Furthermore, in some studies (29), tumor regression degree (mrTRG) on MRI was determined based on changes in tumor size and signal intensity on T1, T2, and WI to predict the outcome of NCRT. Unfortunately, as demonstrated, there is no pathological gold standard.…”
Section: Introductionmentioning
confidence: 99%
“…As a non-invasive imaging technique reflecting microscopic tissue changes, APTw imaging has been applied to diagnose cervical cancer, central nervous system tumors, prostate cancer, endometrial cancer, and rectal cancer (19)(20)(21)(27)(28)(29)(30). APT value is positively correlated with the degree of malignancy, i.e., the higher the degree of malignancy, the greater the APT value.…”
Section: Discussionmentioning
confidence: 99%
“…After nCRT, the ability to achieve tumor reduction or even a pathological complete response (pCR) is observed in approximately 75% of treated patients, whereas the remainder exhibited no treatment response[ 3 , 4 ]. The ability to predict the response to nCRT is important for patients with potentially curable LARC who wish to explore personalized treatment to expand their therapeutic outcomes[ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Functional magnetic resonance imaging (MRI) techniques, such as diffusion-weighted imaging (DWI), can provide additional physiological information about a tumor’s cellular environment, offering great potential to evaluate the therapeutic response to nCRT[ 5 ]. This is because the apparent diffusion coefficient (ADC), a quantitative parameter used to assess water diffusion through tissue in DWI, shows an inverse relationship with tissue cellularity[ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation